Plants for the Future - El-Shemy, Hany (IntechOpen, 2015)
The world has come to understand only recently the importance of plants in our life. Therefore, we have brought together such book chapters that will help strengthen the scientific background of the readers on plants and deliver the message regarding plants for the future, in food security, health, industry, and other areas. This book will add to the scientific knowledge of the readers on the molecular aspects of plants.